PENGARUH PENERAPAN SISTEM ABSENSI FINGER PRINT TERHADAP DISIPLIN PEGAWAI PADA MARKAS KOMANDO DIREKTORAT PENGAMANAN BADAN PENGUSAHAAN BATAM - Risfa Fadila; Maryani Septiana (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2019)
This study aims to examine and analyze the effect of the application of fingerprint attendance on employee discipline in Markas Komando Direktorat Pengamanan Badan Pengusahaan Batam. Data collected through distributing questionnaires to 55 respondents. A sampling technique uses a saturation sampling. The data analysis method used is quantitative analysis using validity and reliability testing, classic assumption test, F test, t test, coefficient of determination and multiple linear regression analysis. The results of data analysis show that 1) the practical dimensions of fingerprint attendance have a positive but not significant effect on employee discipline, 2) the accurate dimension of fingerprint attendance has a positive but not significant effect on employee discipline, 3) high securities fingerprint attendance has a positive and significant effect on employee discipline, 4) the dimensions of fingerprint attendance hardware have a positive but not significant effect on employee discipline, 5) practical, accurate, high security, and fingerprint attendance hardware simultaneously have a positive and significant effect on employee discipline.